Ways to improve land tax administration of legal entities producing in agriculture in our country (Eurasian Research Bulletin, 2023)
This article is devoted to the stages and conceptual foundations of reforms in the agricultural sector, in which reforms in this area are divided into periods. Strategic directions for the development of agriculture in Uzbekistan are proposed. The basics of land tax administration by legal entities producing agricultural products are also disclosed, and a proposal for their improvement has been developed